2021
DOI: 10.1128/jb.00259-20
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Transcriptomic Network Underlying the Wrinkly and Smooth Phenotypes of Vibrio fischeri

Abstract: Vibrio fischeri is a cosmopolitan marine bacterium that oftentimes displays different colony morphologies, switching from a smooth to a wrinkly phenotype in order to adapt to changes in the environment. This wrinkly phenotype has also been associated with increased biofilm formation, an essential characteristic for V. fischeri to adhere to substrates, suspended debris, and within the light organs of sepiolid squids. Elevated biofilm formation is correlated with increased microbial survival to environmental str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Indeed, a study showed that both OP and TR strains were able to form biofilms but with different structures ( 15 ). Another type of adaptive biofilm-associated switching between wrinkly and smooth colony types has been observed in other Vibrio species, such as Vibrio alginolyticus , Vibrio fischeri , and Vibrio cholerae ( 26 28 ). Transcriptomic analysis demonstrated that the wrinkly and smooth phenotypes of V. fischeri differed in their expression profiles, showing that genes related to major biochemical cascades, such as those involved in oxidative stress and membrane transport play roles in the wrinkly phenotype ( 26 ).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Indeed, a study showed that both OP and TR strains were able to form biofilms but with different structures ( 15 ). Another type of adaptive biofilm-associated switching between wrinkly and smooth colony types has been observed in other Vibrio species, such as Vibrio alginolyticus , Vibrio fischeri , and Vibrio cholerae ( 26 28 ). Transcriptomic analysis demonstrated that the wrinkly and smooth phenotypes of V. fischeri differed in their expression profiles, showing that genes related to major biochemical cascades, such as those involved in oxidative stress and membrane transport play roles in the wrinkly phenotype ( 26 ).…”
Section: Introductionmentioning
confidence: 76%
“…Another type of adaptive biofilm-associated switching between wrinkly and smooth colony types has been observed in other Vibrio species, such as Vibrio alginolyticus , Vibrio fischeri , and Vibrio cholerae ( 26 28 ). Transcriptomic analysis demonstrated that the wrinkly and smooth phenotypes of V. fischeri differed in their expression profiles, showing that genes related to major biochemical cascades, such as those involved in oxidative stress and membrane transport play roles in the wrinkly phenotype ( 26 ). At least 124 differentially expressed genes were associated with the wrinkly and smooth variants of V. cholerae , including the vps gene loci for EPS production ( 28 ).…”
Section: Introductionmentioning
confidence: 76%
“…Although vibrio bacterial biofilms can still be devoured, biofilms are generally less susceptible to bacterivory than their planktonic counterparts (cells in the water column) and the capability to produce strong biofilm varies from strain to strain. Recent data supports that predation selects for the hearty biofilm phenotype, and vibrio bacteria can use this strategy to their advantage to settle on various substrates or within their hosts (Chavez-Dozal et al, 2013;Chavez-Dozal et al, 2021).…”
Section: Grazing and Predation Select For More Diverse Phenotypesmentioning
confidence: 93%
“…Biofilm formation in V. fischeri has been closely tied to the success of colonization and proliferation in squid light organs; bacteria first form a biofilm on the outside of the pores that eventually lead into the crypt spaces that lie within the light organ of the squid (Nyholm and Nishiguchi, 2008). Differences exist between symbiotic V. fischeri, and those strains that are free-living and cannot colonize host squids (Nishiguchi et al, 1998;Nishiguchi, 2002;Chavez-Dozal and Nishiguchi, 2011), which may be due to the fact that these free-living strains lack specific regulators for biofilm production that are responsible for colonization and persistence (Chavez-Dozal et al, 2021;Mandel et al, 2009;Thompson et al, 2018). Additionally, biotic factors outside of the squid, such as protozoan grazing, have impacted how V. fischeri (both symbiotic and nonsymbiotic) is susceptible to selective pressures that influence biofilm production and are thought to have driven the diversity of various biofilm phenotypes observed in nature (Chavez-Dozal et al, 2013).…”
Section: Biofilm Regulation and Variability In Vibriomentioning
confidence: 99%
“…Generally, the evolved genetic variants in biofilms were detected primarily as changes in colony morphology, such as smooth and medium colony to small ( Wang et al, 2014 ), mucoid ( McElroy et al, 2014 ; Schwartbeck et al, 2016 ), translucent ( Kaluskar et al, 2015 ; Tipton et al, 2015 ) and wrinkled (or rugose) colony morphologies ( Ali et al, 2002 ; Grau et al, 2005 ; Dragos et al, 2017 ). Among them, wrinkled colony morphology variants dramatically differ in biofilm formation abilities and expression of biofilm-related genes, which is crucial for the process of pathogenesis and fitness improvement ( Gloag et al, 2019 ; Chavez-Dozal et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%